Kepuasan Konsumen Berdasar Kepada Citra Merek dan Kualitas Produk : Survei pada Konsumen Pecel Madiun Mbak Upik di Tasikmalaya - Clarisha Rindiani; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the influence of brand image and quality product towards consumer satisfiction of Pecel Madiun Mbak Upik Tasikmalaya. The type of this study is quantitive method with a survey approach. The population on this study is unknown. Samples on this study 100 people. Data analysis on this study is multiple regression analysis using SPSS ver. 25 software. The result of this study shows that brand image and quality product simultaneously have influence towards consumer satisfiction of Pecel Madiun Mbak Upik Tasikmalaya. Brand image partially has influence towards consumer satisfiction of Pecel Madiun Mbak Upik Tasikmalaya. Quality product partially has influence towards consumer consumer satisfiction of Pecel Madiun Mbak Upik Tasikmalaya.